Integrating Emotional Intelligence, Political Skill, and Transformational Leadership in Construction - Sunindijo, R.Y. (Institute of Research and Community Outreach - Petra Christian University, 2012)
Much research has been conducted to demonstrate the roles of emotional intelligence, political skill, and transformational leadership in the organisational context. However, there is a lack of research that investigates the relationships between the three, particularly in the construction project environment, thus this research attempts to fill this gap. It was hypothesised that emotional intelligence serves as the foundation of these relationships, whilst political skill is the mediator and transformational leadership is the output. Questionnaire survey was used to collect data from three large construction organisations in Australia where 273 valid responses were received. Data were analysed using structural equation modelling method to test the theoretical model. The finding of this research advances theoretical understanding by showing the relationships between emotional intelligence, political skill, and transformational leadership. Practically, it helps construction organisations strategise in recruiting and developing their project personnel.